TEACHER LESSON PREPARATION EVALUATION - MASTALERZ, Elzbieta (Trends in education, 2010)
This article presents lesson planning evaluation as compared to teacher's didactic and educational work evaluation process. The last phase points out important issues, which teacher should take into consideration when analyzing lesson plans.
Keywords: teacher; lesson; evaluation.